Persistence of good living : A'uwe life cycles and well-being in the central Brazilian cerrados - Welch, James R. (Global change / global health, 2023)
"This book is an ethnographic endeavor that explores age identity in the everyday A'uwe (Xavante) experiences at Pimentel Barbosa and Etenhiritipa villages, Central Brazil. It serves as an account of the formal and informal properties of the A'uwe life cycle that contribute to social identity, well-being, health, and environmental engagement. Welch examines the interplay between sociality and environmental relations, emphasizing the distinctiveness of the savanna environment and changing patterns in health conditions. Through environmental analyses, discussion of uses of fire, and the sensitive portrayals of individuals and events, the book develops arguments about how A'uwe understand well-being. The author uses observations from his many years living and working in A'uwe communities to create a portrait of contemporary Amazonian Indigenous people and their environmental and social relations. This account is an argument for an understanding of A'uwe social organization as fundamentally plural, with age statuses and other aspects of social identity being numerous, simultaneous, interdependent, and contingent. The book aspires to be the new ethnographic go-to reference for Xavante society and cultural studies of groups in the Gê language family"--